Pharmacocorrection of Disturbances in the NO System in Experimental Chronic Generalized Periodontitis - Parkhomenko, D. P.; Belenichev, I. F.; Bukhtiyarova, N. V.; Kuchkovskyi, O. M.; Gorchakova, N.; Diachenko, V.; Fedotov, Е. R.; Пархоменко, Дар'я Павлівна; Бєленічев, Ігор Федорович; Бухтіярова, Ніна Вікторівна; Кучковський, Олег Миколайович; Федотов, Євген Рудольфович (My University, 2023)
BACKGROUND: In the light of modern views on the pathogenesis of inflammatory diseases of the oral cavity, a promising direction is the use of agents with metabolitotropic, endothelioprotective, and especially with antioxidant action. AIM: The purpose of this study was to evaluate the effect of a combination of thiotriazoline and L-arginine (1:4) on the parameters of the nitroxidergic system of the blood and periodontium of rats with experimental chronic generalized periodontitis and substantiate further study of this combination. METHODS: Real-time reverse-transcription polymerase chain reaction was used to assess the mRNA expression status of iNOS and nNOS mRNAs. The total content of reduced thiols was also determined by the reaction with Elman’s reagent. RESULTS: We found an increase in the total activity of NOS by 90.01% due to an increase in the expression of iNOS, while a decrease in the expression of its endothelial form was observed (a decrease in the expression of eNOS mRNA by 74.3%) compared with the intact group. An increase in iNOS activity led to an increase in the production of NO, which, under conditions of antioxidant deficiency, is converted into cytotoxic forms (peroxynitrite and nitrosonium ion). CONCLUSIONS: The course administration of Mexidol (250 mg/kg) and, especially, the combination of thiotriazoline and L-arginine (1:4) (200 mg/kg) to animals with CGP, leads to a decrease in the gingival pocket to 6 mm (Mexidol) and to 4 mm against the background almost complete absence of bleeding, swelling, and tooth mobility (combination), and also led to a decrease in iNOS mRNA expression by 65.6% (p < 0.05).
Keywords: Periodontal tissues; Thiotriazoline; L-arginine; Nitroxidergic system; Tiazotic acid; Antioxidant activity